Variations in Rhizopus Species That Play a Role in Making Tempeh in the Bekasi Area - Ardiani, Isnain; Aýun, Qurrota; Nazua, Karina Sheilla (Biosel Biology Science and Education, 2024)
Tempeh is made from fermented soybeans with various types of Rhizopus. The mold used in the making process are known as “ragi”. Ragi plays a key role in converting soybean substrate into healthful nutrition. The tempeh’s ragi may contain more than one species of Rhizopus. This study aims to know a variation of different types of Rhizopus that contributed to the tempeh in Bekasi. The samples are from two different locations are tempeh SMC and JTS. The Methods used in direct planting of PDA media. Macroscopic observations by identifying color, texture and shape of colonies, microscopic slide culture to observe the shape of sporangium, the sporangiophore stalk of columela and sporangiospores. The data is presented in the shape of tables, pictures, and descriptive analysis. Based on the results, found four isolates of the SMC and the two isolate from the JTS. Macroscopic and microscopic in successive ways isolate from tempeh SMC1, SMC2, SMC3, SMC4 has a character similar to R. oryzae, R. stolonifer, R. microsporus and R. oligosporus. As to isolate tempeh JTS1 and JTS2 found similar to R. microsporus and R. oryzae. So, in one tempeh of different locations in the Bekasi, it contains many variations of the Rhizopus. Keywords: Rhizopus, Tempeh, Variation